Evidence of association between early alcohol use and risk of later problems - Vieira,Denise Leite (2007)
OBJECTIVES: To investigate the relationship between age of onset, alcohol consumption patterns and related problems. METHOD: In 2004, one self-administered questionnaire was completed by 1,990 students from the 5th to 11th grades of schools in Paulínia-SP. Data collection was conducted at the classroom without the presence of the teacher. The participation in the study was voluntary and anonymous. RESULTS: Prevalence of lifetime alcohol use was 62.2%. The mean age of first use of alcohol was 12.35 (sd = 2.72) and ranged between 5 and 19 years of age. In 78% of the cases, the first use occurred before the age of 15, and more than 22% of the students reported having tried alcohol before 10 years of age. There were significant differences regarding current pattern of use: those who started earlier consumed more drinks per occasion (p = 0.013) and had more drunkenness episodes in the last 30 days (p = 0.05). A relationship between the age of first alcohol use and the use of tobacco (p = 0.017) and other drugs (p = 0.047) was observed. CONCLUSIONS: Adolescents first use alcohol in early ages, what impacts the current consumption patterns. This study emphasizes the need of actions regarding public alcohol policies in Brazil in order to prevent or delay the initiation of alcohol use and its related problems.